Urban Origins of American Judaism - Moore, Deborah Dash. (Athens : University of Georgia Press, 2014)
The urban origins of American Judaism began with daily experiences of Jews, their responses to opportunities for social and physical mobility as well as constraints of discrimination and prejudice. Deborah Dash Moore explores Jewish participation in American cities and considers the implications of urban living for American Jews across three centuries. Looking at synagogues, streets, and snapshots, she contends that key features of American Judaism can be understood as an imaginative product grounded in urban potentials. Jews signaled their collective urban presence through synagogue construct.
Cover; CONTENTS; LIST OF ILLUSTRATIONS; FOREWORD; PREFACE; INTRODUCTION; CHAPTER 1. SYNAGOGUES; CHAPTER 2. STREETS; CHAPTER 3. SNAPSHOTS; CONCLUSION; NOTES; BIBLIOGRAPHY; INDEX; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y; Z
Description based upon print version of record.
Description based on print version record.
Keywords: Judaism -- United States -- History; RELIGION / Judaism / General; Electronic books